Tube-Tests of Eichhornia crassipes and Pistia stratiotes Extracts as Bacterial Anti-Biofilm - Lia Yulia Budiarti; Farida Heriyani; Shofia Hilwa Ihsanti; Fadya Rahma Sari; Yogi Waskito Aji; Maulidia Khairada Amalia (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
Bacterial biofilms have strong adhesion to medical devices and are resistant to disinfectants, potentially triggering nosocomial infections. One promising approach involves the use of alternative phytochemical-based disinfectants. Eichhornia crassipes (E. crassipes) and Pistia stratiotes (P. stratoites) plants are known to possess antibacterial compounds; however, their anti-biofilm potential remains to be studied. This experimental study aimed to assess the antibiofilm potential of ethanol extracts of E.crassipes and P.stratiotes using a test tube method. The combination extract (EC+PS) was prepared at concentrations of 6.25% - 100% and tested in triplicate along with a control. Its ability was tested on three ATCC bacterial strains (S. aureus, E. coli, and P.aeruginosa) that form biofilms; confirmed by the growth of black colonies on Congo Red Agar (CRA). Qualitative observations determined the Minimum Biofilm Inhibitory Concentration (MBIC), revealing effective inhibition of 12.5% ​​for E. coli and S. aureus, and 25% for P. aeruginosa. ANOVA analysis of biofilm intensity based on the Mean Gray Value (MGV) parameter showed significant variation between the EC+PS treatment and the control group (p < 0.05). Duncan's post hoc test showed the antibiofilm effect of EC+PS was comparable to chlorine: 75% for S. aureus and 100% for E. coli and P. aeruginosa (p < 0.05). In conclusion, the anti-biofilm activity of E. crassipes and P. stratoites shows promise as alternative disinfectants.